Extramedullary Waldenström macroglobulinemia. Issue 2 (19th November 2014) - Banwait, Ranjit; Aljawai, Yosra; Cappuccio, Joseph; McDiarmid, Serena; Morgan, Elizabeth A.; Leblebjian, Houry; Roccaro, Aldo M.; Laubach, Jacob; Castillo, Jorge J.; Paba‐Prada, Claudia; Treon, Steven; Redd, Robert; et al.
<x xml:space="preserve">Abstract</x> Disease assessment in Waldenstrom Macroglobulinemia (WM) is dependent on the percent involvement of B‐cell neoplasm in the bone marrow and IgM paraprotein in the serum. A subset of patients also demonstrates extramedullary involvement, which is infrequently examined. The role of extramedullary involvement in the diagnosis and prognosis of WM is poorly understood. The purpose of this study is to report the characteristics of WM patients with extramedullary disease (EMD). Nine hundred and eight‐five patients with WM were evaluated at one academic center and the presence of EMD was assessed in these patients. Forty‐three (4.4%) patients were identified to have EMD. Nine (21%) patients presented with involvement at WM diagnosis, while 34 (79%) developed EMD post‐therapy for WM. Most frequent EMD sites involved were pulmonary (30%), soft tissue (21%), cerebrospinal fluid (23%), renal (8%), and bone (9%). The median overall survival at 10 years was 79% (95% CI: 57–90%). This is the first study to describe the clinical characteristics, response and overall survival in patients with extramedullary WM. Further studies to define the molecular characteristics of this entity and mechanisms of its development are warranted. Am. J. Hematol. 90:100–104, 2015. © 2014 Wiley Periodicals, Inc.